The technical-tactical preparation of the boxers from Sancti Spíritus - Juan Manuel García Hernández; Giraldo Machuat Santana; Bárbaro Fernández Jimenez; Pedro Omar Toledo Díaz (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2018)
The investigative work presented is part of the daily work of the group of trainers that works in the Provincial Boxing Academy in the province of Sancti Spíritus. The problem investigated responds to the technological demands that exist at the provincial level, with the objective of applying a set of technical-tactical actions to raise the level of preparation of the boxers of Sancti Spiritus that allows to obtain satisfactory results in the competitive order. The diagnosis was developed based on the results of the technical tests of the participation of the boxers from Sancti Spiritus in the Playa Girón National Championships in the 2013-2016 cycle. The final results are compared with those issued by the specialists of the National Technical Commission in the present Playa Girón National Championship held in December 2017, in the Sala Yara of the Province of Sancti Spíritus. The population that used for this investigation is made up of 20 elite category boxers from the province of Sancti Spíritus. The achievements correspond to the work done collectively and individually from the shortcomings and potentials presented by the investigated boxers from Sancti Spiritus. Therefore, it was possible to demonstrate that taking into account the behavior of the main dimensions and indicators of the technical tests, good competitive results can be obtained and that it facilitated the differentiated work with each boxer taking into account the scientific and technical advances at our disposal. In order to comply with this research, theoretical, empirical and mathematical methods were used; among them we can mention: Historical-logical, synthesis analysis, inductive deductive, observation, interview, pre-experiment and descriptive statistics.